STUDI MENGENAI BRAND LOYALTY DALAM MENINGKATKAN BRAND EQUITY KARTU PRABAYAR GSM PT. INDOSAT KOTA SEMARANG - Hasanah, Emy Yatul; Mudiantono, Mudiantono; Soesanto, Harry (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2008)
Mobile phone industry is experiencing rapid growth in the last two decades, both in the developed countries or developing. In any mobile phone has changed the map of the telecommunications industry drastically. Various brands appear and compete closely. This raises the question